Era Digitalisasi: Membawa Kesenjangan, Ide Sulit Berkembang? - Junaedi, Nurasikin; Asbari, Masduki; Naja, Rif'atun; Jodyapati, Satrio (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this study is to find out something that can eliminate a group in the era of Digitalization. In this study report, using descriptive qualitative methods by taking notes, because the source of the data obtained by listening to oral narration from the Gita Wirjana youtube channel entitled "Emergency management of ideas and ethics" presented by him. The results of this study explain that this world will continue to change, one of which is in the world of technology that is growing very rapidly, for example to get information that is so easy to get at this time. However, behind the rapid development, there is a bad impact caused and it is very concerning if it continues to be left unchecked. Ideas are difficult to accept and develop, good ideas are clouded by habitual behaviors, bringing gaps between individuals. This research began with the emergence of individualism and excessive perception. The era of digitalization can change the way every individual lives their lives. This change in reality is happening and developing very fast among the people. One of them is in the college environment.